نظرةٌ لغويةٌ تاريخيةٌ في إنجيل برنابا - Yaacob, Solehah@Nik Najah Fadilah (2017)
The copy of Bible is carbon dated circa 1500 until 2000 years discovered in Turkey in 2000 century A.D has unlocked the paradigm thinking towards the Gospel of Barnabas. The silence of Muslim side on the issue of Gospel of Barnabas since its translated into Arabic language then published by al-Manar journal was not provide the great impact to the research. Linguistically and historically has proved that there is a similarity between the provisions of the Gospel of Barnabas and Islamic law, as well as alleged by some historians that this gospel formats after Divine Comedy published by A. Dante Alighieri in 1320 AD. Thus, some questions raise: Does the manuscript Italian of the gospel which currently in Austrian National Library in Vienna since 1738 that was before in Amsterdam in 1709 is the oldest translation`s copy? We assume that it has been translated into Italian from the original version which was not an easy task to be determined of its originality especially the original language was ancient language? Thus, the research aims to reveal some mysteries of the gospel of Barnabas and its connection with the Bible (The Canonical Books) through the comparison and analytical thinking approaches methods.